Analisis Swot Pada Quality Assurance Produk Wiring Harnes Di PT Cipta Mandiri Wirasakti - Ainun Fadilah Lubis; Andri Nurtantiono (Excellent, 2025)
The main objective of this research is to analyze the SWOT analysis of Wiring Harness product quality assurance at PT Cipta Mandiri Wirasakti and identify more effective quality improvement strategies. This research used qualitative methods with a descriptive approach through observation and interviews. The results indicate that internal factors supporting the development of quality assurance include a competent workforce, an integrated quality management system, and partnerships with trusted suppliers. Inhibiting factors include limited technological infrastructure and price competition. Possible strategies include improving the quality and number of employees, maintaining good product quality, and maintaining product quality control.